Determining the Optimal Return of a Sharia-Compliant Stock Investment Portfolio in the Employment Social Security Agency - Reyzal Narendra (KEDJATI Journal of Islamic Civilization, 2025)
The Employment Social Security Agency (BPJS Ketenagakerjaan) is progressively implementing Sharia principles across its operational activities, including the management of equity investments in Sharia-compliant financial instruments. This study aims to determine the optimal Sharia-compliant stock investment portfolio for the Jakarta Islamic Index (JII) using a quantitative, descriptive approach and portfolio optimisation techniques. The analysis employs the Markowitz mean-variance model and the Single Index Model, based on monthly closing prices of Sharia-compliant stocks listed on the JII from 2019 to 2023. The results indicate that the Markowitz model generates an optimal portfolio consisting of ADRO (24.41%), ICBP (0.13%), BPRT (37.76%), and ANTM (37.70%), with an expected return of 0.63% and a portfolio risk of 0.35%. In comparison, the Single Index Model produces a more diversified portfolio comprising ADRO (19.62%), ANTM (23.50%), BPRT (19.65%), INCO (14.69%), ITMG (12.54%), EXCL (5.02%), TLKM (2.89%), and KLBF (2.09%), yielding an expected return of 0.48% and a risk level of 0.23%. Thus, the findings demonstrate that the portfolio constructed using the Markowitz model provides a more optimal risk-return trade-off and is therefore recommended as the preferred Sharia-compliant investment strategy for BPJS Ketenagakerjaan.